2003
DOI: 10.1590/s0104-11692003000500005
|View full text |Cite
|
Sign up to set email alerts
|

Mulher e trabalho: a história de vida de mães trabalhadoras de enfermagem

Abstract: This study focused on the life of women who are both mothers and nursing professionals, applying the method of life history. The goals were: to describe the every day life of these professionals; to identify the influence of the profession on these women and to analyze the perception of this reality based on their history of life. Data partial analysis showed that the profession interferes in women's lives, considering their type of activity, and that quite often it changes deeply the family's daily routine. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
25

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 2 publications
0
9
0
25
Order By: Relevance
“…Thus, it was found that both the nurses and the nursing technicians expressed that the factor recognition, composed of feelings of indignation, injustice and devalorization, was at critical levels. These feelings are probably related to the lack of working conditions they are exposed to in the public hospitals, such as the lack of human resources, equipment and materials, which generates an overload for the workers and a lack of care for the patients (6,13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it was found that both the nurses and the nursing technicians expressed that the factor recognition, composed of feelings of indignation, injustice and devalorization, was at critical levels. These feelings are probably related to the lack of working conditions they are exposed to in the public hospitals, such as the lack of human resources, equipment and materials, which generates an overload for the workers and a lack of care for the patients (6,13) .…”
Section: Discussionmentioning
confidence: 99%
“…The work carried out by the nursing team in this environment, although essential, has little social recognition; is undervalued and invisible to the other health professionals and the patients (1)(2)6) . Additionally, in recent years in Brazil, mainly in the public health institutions, nursing care in general has been penalized with a deficiency of human and material resources that directly influences the quality of care provided to the population (1)(2) .…”
mentioning
confidence: 99%
“…Assim, assumiram profissões tais como: professora e enfermeira, para as quais se julgavam mais preparadas, como também porque eram as mais aceitas pela sociedade. Entretanto a relação mulher-trabalho-família nunca se tornou harmoniosa, os conflitos sempre estiveram presentes 10 . O mesmo estudo ressalta ainda que os múltiplos papéis assumidos pela maioria das mulheres no exercício profissional, tendem a remetê-las a determinadas situações em que se sentem impotentes e frustradas por não conseguirem conciliar seus inúmeros afazeres.…”
Section: Revisão De Literaturaunclassified
“…O mesmo estudo ressalta ainda que os múltiplos papéis assumidos pela maioria das mulheres no exercício profissional, tendem a remetê-las a determinadas situações em que se sentem impotentes e frustradas por não conseguirem conciliar seus inúmeros afazeres. Além disso, ao chegar ao seu local de trabalho se deparam com dificuldades que muitas vezes não são de sua competência resolvê-las 10,11 . Tendo em vista o trabalho das enfermeiras nos hospitais observa-se que elas podem estar expostas a ambientes de trabalho intensamente insalubres, tanto no sentido material quanto subjetivo e, por estarem submetidas a condições de trabalho precárias e à baixa qualidade de vida, são expostas a situações nas quais a manutenção da saúde está prejudicada…”
Section: Revisão De Literaturaunclassified
See 1 more Smart Citation